Side-slip angle estimation based lateral dynamics control for omni-directional vehicles with optimal steering angle and traction/brake torque distribution. (September 2015) - Li, Boyuan; Du, Haiping; Li, Weihua; Zhang, Yongjun
Highlights: Lateral dynamics control of omni-directional vehicles. Side slip angle estimation based slip angle control and friction limit criteria. Optimal yaw rate control and slip angle control. Optimal distribution of longitudinal tire force and lateral tire force. Optimal mapping from individual tire force to eight individual actuators. Abstract: The omni-directional vehicle is an innovative vehicle that has an in-wheel steering motor and in-wheel driving motor installed with each wheel. Each wheel of the omni-directional vehicle can be independently controlled so that the vehicle's mobility, handling and stability performance is greatly improved. Various control strategies such as active steering control, direct yaw moment control, and four-wheel drive control have been proposed to improve vehicle handling and stability performance. Most research, however, has only been done for traditional internal combustion vehicles, and the controller performance is constrained by the limitation of the actuators. In recent years, research has looked at the optimal distribution and control of the eight actuators, the steering angle of each wheel and the traction or brake torque of each wheel independently and in real time for an omni-directional vehicle. In this paper, an innovative side-slip angle estimation method developed for an omni-directional vehicle with in-wheel steering motors is applied to construct the side-slip angle controller and to determine the friction limit criteria for the overall control system. Optimal steering and driving actuator distribution and control is developed to improve the yaw rate response and body slip angle response of the vehicle. Finally, simulations are used to validate the proposed control method.